Associations between media exposure and mental health among children and parents after the Great East Japan Earthquake. Issue 1 (31st December 2023) - Ohnuma, Asami; Narita, Zui; Tachimori, Hisateru; Sumiyoshi, Tomiki; Shirama, Aya; Kan, Chiemi; Kamio, Yoko; Kim, Yoshiharu
ABSTRACT: Background: Exposure to natural disaster media coverage is associated with mental health problems, but its long-term impacts are still unclear. Also, no study has analysed the psychological impact of exposure to natural disaster media coverage among children who are generally sensitive to threatening events. Objective: We aimed to examine how television images of victims after the 2011 Great East Japan Earthquake were associated with mental health among children and their parents. Methods: In 2012, questionnaires for sociodemographic factors were distributed to 2053 families. Parents who provided written consent were contacted in 2013 and invited to provide information on mental health problems (outcome) and retrospectively provide information on television watching at the time of the earthquake (exposure). We used data from 159 parents who completed the survey as the final sample. We used a dichotomous variable to evaluate exposure to media coverage. Multivariable regression was used to examine the association between exposure to television images of victims and mental health, adjusting for potential confounders. Bias-corrected and accelerated bootstrap confidence intervals (CIs) were used. Results: Exposure to television images of victims was significantly associated with worse psychopathology among children ( β, 1.51; 95% CI, 0.07–2.96) and greater psychological distress among their parents ( β, 1.49; 95% CI, 0.28–2.70). Child psychopathology and parental psychological distress were significantly correlated ( r = 0 .36, p < .001). Conclusions: Exposure to television images of disaster victims may produce long-term impacts on mental health among children and their parents. To reduce the likelihood of mental health problems associated with disasters, clinicians may recommend reducing exposure to television images of victims. HIGHLIGHTS: Television images of victims after the 2011 Great East Japan Earthquake were associated with worse psychopathology among children in 2013, adjusted for potential confounders. Similar associations were found in psychological distress among their parents. Child psychopathology and parental psychological distress were correlated with each other.